SENSOR SYSTEM DESIGN FOR PROPELLER TEST BENCH - Ihsan, Nurul; Dermawan, Denny; P, Lazuardy Rahendra (Institut Teknologi Dirgantara Adisutjipto, 2021)
The sensor system is a system that functions to detect signals that come from changes in energy such as electrical energy, physical energy, chemical energy, biological energy, mechanical energy, and so on. The propeller test bench is an propeller performance testing platform prior to propeller installation on an aircraft to ensure engine suitability. The purpose of this design is to test the performance capability of the engine with the right sensor system measurement tool so that it can generate the value of thrust, rpm speed, and the temperature of an engine which will be designed to be used in the learning process to support propulsion practicum activities. The method used in this research is an experimental method of sensor system design. The design of the sensor system consists of a tachometer as a rpm measurement sensor, a thermostat as a sensor to measure the temperature of the propeller spool and temperature of the engine fin, and also a load cell as a sensor to measure the thrust value.The sensor system test results were then validated using the measurement results by the sensor manufacturer. The test was carried out on a wood-type propeller measuring 22 x 8 chords 4,5 cm and 5 cm. Based on the test results, it is known that the chord wood type propeller is 4,5 cm, at the maximum rpm is 7021.7, the resulting thrust value is 6.75. In testing the 5cm chord wood type propeller shows the maximum speed of 6977.5 produces a thrust of 6.95. Validation was carried out on the measurement results of rpm and thrust, the average error factor obtained for 4,5 cm chord wood type propeller was 0.783%, while for 5 cm chord wood type propeller the average error factor obtained was 1.0582%. From the resulting average error, it can be concluded that the measuring instrument for this sensor system has good accuracy